Characterisation of fine-grained tailings from a marble processing plant and their acute effects on the copepod Calanus finmarchicus. (February 2017) - Farkas, Julia; Altin, Dag; Hammer, Karen M.; Hellstrøm, Kaja C.; Booth, Andy M.; Hansen, Bjørn Henrik
Abstract: Submarine tailing disposal (STD) of mining waste is practiced as an alternative to land fill disposal in several countries. Knowledge regarding the environmental implications of STD on fjord and other marine ecosystems, including the pelagic environment, is scarce. In this study, we characterised the particle shape, size and metal content of the fine-grained fraction of tailings (FGT) from a Norwegian marble processing plant and investigated their acute toxicity and impact on feeding rate in adult Calanus finmarchicus . Initial tailing dispersions with a concentration of 1 mg mL −1 contained approximately 72 million particles, with 62% of particles between 0.6 and 1 μm in size. After a sedimentation time of 1 h, 69% of the particles between 0.6 and 5 μm remained dispersed, decreasing to 22% after 6 h. When subjected to low energy turbulence in exposure experiments, the formation of fragile agglomerates was observed. The FGT contained Al, Mn, Fe and Ni, with no detectable dissolution occurring during the 48 h exposure period. Acute exposure (up to 5 g L −1 ) to FGT caused no mortality in C. finmarchicus . Similarly, feeding rates determined during a 40 h depuration period, were not significantly impacted. However, surface attachment and uptake of FGT into the digestive tract of the copepods was observed. This indicates that, whilst marble FGT are not acutely toxic to copepods, chronic effects such as impacts on organism's energy budgets could occur, highlighting the need for further research on potential sublethal effects in organisms exposed to fine inorganic particles. Graphical abstract: Highlights: Submarine tailing disposal is practised in Norway. Characterisation and effects of tailings from a marble processing plant on zooplankton. Tailings contain a large amount of fine particles (0.6–2 μm). Fine grained tailings are not acutely toxic to the copepod Calanus finmarchicus . Surface attachment and ingestion of fine grained tailing particles was observed.